Impact of front line demonstrations on productivity of Okra cv. Gujarat Okra-2 in Panchmahals district of middle Gujarat (Indian Journal of Arid Horticulture, 2013)
The present study was carried out at Panchmahals district of middle Gujarat during 2011-12. Okra is one of the most  important vegetable crop of the country and India is the largest producer in the World. The development of the Agriculture is  primarily depends on the application of the scientific technologies by making the best use of available resources. One of the  major constraints of traditional okra farming is low productivity because of non-adoption of advanced technologies. To  increase the production, productivity and quality of agricultural produce, Front Line Demonstrations is conducting at various  farmers' field. All the recommended practices were provided to the selected farmers. The data related to cost of cultivation,  production, productivity, gross return and net return were collected as per schedule and analyzed. Results of the present study  revealed that the improved variety of Okra Gujarat Okra-2 recorded the higher yield (105.90 q/ ha) as compared to local  check (87.60 q/ ha) traditionally grown by the farmers. The percentage increase in the yield over local check 20.89 was  recorded. The technology gap in terms of productivity (9.1 q/ha) were computed. The technology index values 7.91 % was  recorded. The results of study indicated the gap existed in the potential yield and demonstration yield is due to soil fertility  and weather conditions. By conducting Front Line Demonstrations (FLDs) of proven technologies, yield potential of Okra  can be increased upto great extent. This will substantially increase the income as well as the livelihood of the farming  community
Keywords: Front Line Demonstrations; local check; Okra; Technology; Yield